Serum myristic fatty acid negatively correlates with anti-inflammatory adiponectin/leptin ratio in obese adolescents: effects of long- term therapy - de Piano-Ganen, Aline; Landi Masquio, Deborah Cristina; R. Dâmaso, Ana; Missae Oyama, Lila; Estadella, Debora; Chamas, Andreia; Penha Oller do Nascimento, Claudia Maria (O Mundo da Saúde, 2017)
Obesity is related to metabolic disorders partially mediated by inflammatory state. In this way, adiponectin/leptin ratio is considered an anti-inflammatory biomarker related to cardiovascular risks. Evidence suggest that decrease in saturated fatty acid intake is an important dietary recommendation to reduce cardiovascular risk factors. Thus, the purpose of the present study was to evaluate if serum myristic fatty acid can modulate metabolic profile and inflammatory process in obese adolescents after weight-loss therapy. Twenty-nine obese post-pubertal obese adolescents, aged 14 to 19 years, were submitted to the long-term interdisciplinary treatment, including physical exercise, clinic, nutritional and psychological intervention. The blood samples were collected to glycaemia, insulin, lipid profile, leptin and adiponectin analysis. Serum fatty acid composition was performed by technical of chromatography in fizzy phase. The therapy promoted significant improvement in body mass, BMI, subcutaneous and visceral fat, insulin, lipid profile, leptin and leptin/adiponectin ratio. Significant decrease in myristic fatty acid was observed. Simple linear regression analysis showed that myristic fatty acid was positively associated with changes in triglycerides and very low density lipoprotein cholesterol, and was negatively associated with adiponectin/leptin ratio. In summary, we observed that long-term weight loss therapy was effective to improve metabolic/inflammatory profile and serum myristic fatty acid. Moreover, our results suggested the relation between changes in serum myristic fatty acids with the anti-inflammatory adiponectin/ leptin ratio, which may modulate metabolic and inflammatory process related to obesity.